2012
DOI: 10.26719/2012.18.6.607
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the Islamic Republic of Iran: an integrated analysis from 1981 to 2007

Abstract: Although the rate of suicide is low in Muslim countries, there is evidence that it is increasing. An integrated analysis was made of data on suicide attempts (nonfatal and fatal) from studies carried out in the Islamic Republic of Iran from 1981 to 2007. Of 54 published studies concerning suicide, 48 (covering 26 768 cases of attempted suicide) satisfied the inclusion criteria. The weighted mean rate of suicide attempts was 26.5 per 100 000 and the average rate of death by suicide was 6.7 per 100 000. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…One noteworthy aspect in the area of mental health is the increasing trend of suicide and suicidal attempts in Iran that varies in relation to gender [ 33 ]. Although the rate of committed suicide is greater in men than in women, there is a higher frequency of suicide attempts among Iranian women, a situation showing an increasing trend in recent years [ 34 ]. Violence and family disputes are among the most important reasons for attempted suicides, especially among married women [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…One noteworthy aspect in the area of mental health is the increasing trend of suicide and suicidal attempts in Iran that varies in relation to gender [ 33 ]. Although the rate of committed suicide is greater in men than in women, there is a higher frequency of suicide attempts among Iranian women, a situation showing an increasing trend in recent years [ 34 ]. Violence and family disputes are among the most important reasons for attempted suicides, especially among married women [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Study of the global patterns of mortality in young people has shown that suicide is the second leading cause of death in the 15-19 years age group ( 16 ). Analysis of data from studies on suicide attempts carried out in the Islamic Republic of Iran between 1981 to 2007 showed that the mean age of suicide attempters was 25 years ( 12 ). A study of suicide attempts in Hamedan province reported that the suicide attempt rate was highest in the age group of 15-24 years with an incidence rate of 536 cases per 100000 population ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are also seasonal differences in suicide between the United States and Persia. Instead of spring having the highest suicide rate, as is the case in the United States, summer has been reported as a season when the highest suicide rate is reported in Persia, with the rate being approximately 13% higher than in other seasons (Ghafarian Shirazi et al., ). Thus, although similar, suicide manifests differently in Persia, and thus studies testing whether findings generalize across cultures are warranted.…”
mentioning
confidence: 99%